Do babies and adults feel the same in an aquatic programme for babies? - Gil Pla-Campas; Verónica Jiménez; Francesc Martínez-Olmo; Montse Benlloch (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background. Interest in aquatic programs for babies has grown significantly, with many families participating worldwide. While numerous studies have examined the effects of these programs on motor development or aquatic learning, little attention has been given to the emotional experiences of the interaction. Understanding how emotions appear in each subject and how they influence the learning process opens a valuable area of exploration in early childhood motor development.